Implementasi Gerakan Tujuh Kebiasaan Anak Indonesia Hebat dalam Pembentukan Karakter Tanggung Jawab Siswa di Sekolah Dasar Negeri Jombor 01 - Purbosari, Para Mitta; Fitriyanto, Chesya Rahmadani; Oktavia, Diah Ayu; Noviyanto, Reza Wahyu; Meytasari, Nanda Anisa (LPPM Universitas PGRI Argopuro Jember, 2026)
This study aims to describe the implementation of the Seven Habits of Great Indonesian Children (G7KAIH) in shaping the character of responsibility among students at SD Negeri Jombor 01. The research employed a descriptive qualitative approach with data collected through observations, interviews, Focus Group Discussions (FGD), and documentation. The research subjects included the principal, classroom teachers, and students from grades II to VI who were actively involved in the program. The findings show that the seven habits, namely waking up early, worshiping, exercising, consuming nutritious food, loving to learn, engaging in community activities, and sleeping early, have been systematically integrated into various school programs such as SIAP, SOJALI, SANGAJI, SEHAT, DIGIDAY, KREATIF, GEMAYUR, GEMARI, and SOSIAL. The implementation of these habits has had a positive impact on the development of students’ responsibility character, particularly in the areas of discipline, academic responsibility, healthy lifestyle awareness, and social empathy. The success of this implementation is strengthened by the collaboration among the Four Centers of Education, namely the school, parents, community, and social media. Based on these findings, G7KAIH can be considered an effective and feasible model for character education in primary schools, especially in fostering responsibility through continuous and structured habituation practices.